Fracture failure analysis and research on drive shaft of positive displacement motor. (December 2019) - Liu, Yang; Lian, Zhanghua; Xia, Chengyu; Qian, Liqin; Liu, Shaohu
Abstract: In this paper, microstructures and mechanical properties of the fractured drive shaft are investigated by visual inspection, metallographic analysis, scanning electron microscopy, and tensile and impact tests. The composition, structure and mechanical properties of the drive shaft materials are tested to meet the standards. The fracture surface is mainly characterized by dimples and a small amount of quasi-cleavage by microscopic analysis, which indicates that the fracture surface is dominated by ductile fracture. At the bottom of the sample pit, there are a large number of grey inclusions, which are turned to be iron oxides through EDS spectrum analysis. So, the existence of a large number of iron oxide inclusions in the metal will inevitably have a serious impact on the performance of drive shaft. The finite element analysis shows that the stress on the cylindrical surface of the external thread near the shoulder will gradually increase greatly and the rupture risk will increase with the increase of the torque and that it will also fails due to the relatively high stress on the root of the first tooth of thread. The maximum stress near the thread shoulder is close to the yield limit of the material when the borehole curvature is larger and the bending load will lead to stress concentration on the optical axis section at the shoulder, which will affect the safety of drive shaft. Because there are a large number of inclusions in raw materials and the conditions in the well are complex, the carrying capacity of drive shaft decreases and fracture of the drive shaft is finally caused. The maximum stress value of the improved drive shaft is lower than that before the improvement through the comparative analysis. It shows that the safety factor and service life of the drive shaft can be improved by the improved design. Highlights: Did the testing of composition and mechanical properties about material of shaft. The area had good toughness through scanning electron microscopy of sample. Carried out the three-dimension simulation of M119 × 4–6g. The largest stress was at the regions of actual fracture site. Mechanical strength analysis and structural improvement of drive shaft.